A systematic review and meta‐analysis of outcomes after elective surgery for ulcerative colitis. (1st September 2020) - Baker, D. M.; Folan, A.‐M.; Lee, M. J.; Jones, G. L.; Brown, S. R.; Lobo, A. J.
Abstract: Aim: Approximately 20%–30% of patients with ulcerative colitis (UC) will undergo surgery during their disease course, the vast majority being elective due to chronic refractory disease. The risks of elective surgery are reported variably. The aim of this systematic review and meta‐analysis is to summarize the outcomes after elective surgery for UC. Methods: A systematic review was conducted that analysed studies reporting outcomes for elective surgery in the modern era (>2002). It was prospectively registered on the PROSPERO database (ref: CRD42018115513). Searches were performed of Embase and MEDLINE on 15 January 2019. Outcomes were split by operation performed. Primary outcome was quality of life; secondary outcomes were early, late and functional outcomes after surgery. Outcomes reported in five or more studies underwent a meta‐analysis of incidence using random effects. Heterogeneity is reported with I 2, and publication bias was assessed using Doi plots and the Luis Furuya‐Kanamori index. Results: A total of 34 studies were included (11 774 patients). Quality of life was reported in 12 studies, with variable and contrasting results. Thirteen outcomes (eight early surgical complications, five functional outcomes) were included in the formal meta‐analysis, all of which were outcomes for ileal pouch–anal anastomosis (IPAA). A further 71 outcomes were reported (50 IPAA, 21 end ileostomy). Only 14 of 84 outcomes received formal definitions, with high inter‐study variation of definitions. Conclusion: Outcomes after elective surgery for UC are variably defined. This systematic review and meta‐analysis highlights the range of reported incidences and provides practical information that facilitates shared decision making in clinical practice.